Plant functional traits affect competitive vigor of pasture grasses during drought and following recovery. Issue 7 (2nd July 2022) - Chieppa, Jeff; Power, Sally A.; Nielsen, Uffe N.; Tissue, David T.
Abstract: Grassland biomass production is strongly linked with the timing and intensity of precipitation events. While the direct effects of precipitation patterns on grasses are well‐studied, less is known regarding plant–plant interactions during different phases of drought (i.e., dry down vs. recovery). Here, we examined how the intensity and timing of drought affected biomass production, traits related to growth rate and competitive vigor (specific leaf area [SLA], leaf dry matter content [LDMC], and height [HT]), and competitive effects in three common pasture grasses. Each species was grown alone (one individual per 45‐L planter) or with competition (one individual of each species per 45‐L planter) under three different drought types: (1) "short‐term" drought where water was withheld until the first species reached stomatal closure; (2) "prolonged" drought where water was withheld until all three species reached stomatal closure; and (3) "repeated" short‐term drought where water was withheld until the first species reached stomatal closure, plants were rewatered to capacity, and then, the drought was repeated. In all three drought types, replicates were assessed for biomass and traits pre‐ and post‐rewatering to represent the "resistance" and "recovery" phases of drought, respectively. Overall, we found (1) competitive interactions during phases of drought were primarily mediated by plant HT and LDMC, not SLA; (2) the severity and frequency of drought were key factors in describing plant–plant interactions during phases of drought; and (3) interspecific differences in traits and trait responses to drought phases were key in predicting plant–plant competition. Such shifts in competition interactions associated with interspecific trait responses to drought and during recovery from drought are likely to have significant effects on the productivity and composition of multispecies, grass‐dominated plant communities.